Comparison of cryofixation and aldehyde fixation for plant actin immunocytochemistry: aldehydes do not destroy F-actin - Vitha, S; Baluska, F; Braun, M; Samaj, J; Volkmann, D; Barlow, P W (The Histochemical journal, 2000)
For walled plant cells, the immunolocalization of actin microfilaments, also known as F-actin, has proved to be much trickier than that of microtubules. These difficulties are commonly attributed to the high sensitivity of F-actin to aldehyde fixatives. Therefore, most plant studies have been accomplished using fluorescent phallotoxins in fresh tissues. Nevertheless, concerns regarding the questionable ability of phallotoxins to bind the whole complement of F-actin necessitate further optimization of actin immunofluorescence methods. We have compared two procedures: (1) formaldehyde fixation and (2) rapid freezing and freeze substitution (cryofixation), both followed by embedding in low-melting polyester wax. Actin immunofluorescence in sections of garden cress (Lepidium sativum L.) root gave similar results with both methods. The compatibility of aldehydes with actin immunodetection was further confirmed by the freeze-shattering technique that does not require embedding after aldehyde fixation. It appears that rather than aldehyde fixation, some further steps in the procedures used for actin visualization are critical for preserving F-actin. Wax embedding, combined with formaldehyde fixation, has proved to be also suitable for the detection of a wide range of other antigens.
Keywords: Cryopreservation; rostliny; Fluorescent Antibody Technique; rostlinné buňky; aktiny; fixace tkání; Actins; kryoprezervace; Aldehydes; Tissue Fixation; Plant Cells; Plants; fluorescenční protilátková technika; aldehydy